Why are Trade Agreements Regional? - Ben Zissimos (Fondazione Eni Enrico Mattei (FEEM), 2007)
This paper shows how distance may be used to coordinate on a unique equilibrium in which trade agreements are regional. Trade agreement formation is modeled as coalition formation. In a standard trade model with no distance between countries, a familiar problem of coordination failure arises giving rise to multiple equilibria; any one of many possible trade agreements can form. With distance between countries, and through strategic interaction in tariff setting, regional trade agreements generate larger rent-shifting effects than non regional agreements, which countries use to coordinate on a unique equilibrium. Under naive best responses, regional agreements give way to free trade.
Keywords: F02; F13; F15; C72; 330; Coalition; Coordination; Regionalism; Preferential Trade Agreement; Trade Liberalization; Handelsregionalismus; Außenhandelsliberalisierung; Optimalzoll; Koordination; Theorie